ANTESEDEN DAN KONSEKUENSI DIGITALISASI PELAPORAN KEUANGAN PADA UKM BIDANG REAL ESTATE DAN KONSTRUKSI DI JAWA TENGAH - Ida Farida; Aryanto Aryanto (Pusat P2M Politeknik Negeri Batam, 2025)
Adoption of digital-based accounting technology will help SMEs to produce quality financial information so that it can be a reference for business strategy decisions to improve business performance. The purpose of this study is to analyze the influence of antecedent variables, namely accounting knowledge, business experience, business strategy on the digitalization of financial reporting, and the consequences of digitalization of financial reporting on company performance in SMEs in the Real Estate and Construction Sector in Central Java. This study analyzes data using a variant-based Structural Equation Model (SEM) statistical method approach, with an alternative Partial Least Square (PLS) approach. The results of this study reveal that accounting knowledge and business strategy have a significant impact on the digitalization of financial reporting. In addition, the digitalization of financial reporting contributes significantly to company performance. However, business experience does not show a significant influence on the digitalization of financial reporting in SMEs.